Promoting Knowledge in Basic Principles of Ethics for Accounting Professionals Case Study: Bachelor's Degree Student in Accounting Rajamangala University of Technology Lanna Tak - Chunkeaw, Yuparat; Impitak, Yopharat (Journal of Industrial Business Administration, 2024)
The objectives of this research were to study students'opinions on promoting knowledge in the basic principles of ethics for accounting professionals in accordance with the Federation of Accounting Professions' regulations regarding ethics for accounting professionals 2018 and to study the differences between students with a 4-year study plan and students with a transfer study plan in promoting knowledge in the basic principles of ethics for accounting professionals. The samples of this research were undergraduate students in the accounting field, Faculty of Business Administration and Liberal Arts, Rajamangala University of Technology Lanna Tak amount 115 people. The questionnaires wereused a tool to collect data. Mean with standard deviation and t-test statistics (t-test) were used to analysis the data. The results of the research found that students' opinions towards promoting knowledge in the basic principles of ethics for accounting professionals according to the Federation of Accounting Professions regulations regarding ethics for accounting professionals 2018 had the most overall ( = 4.60, S.D. = 0.15) and it was found that the study plans of different students had not a different need to promote knowledge in the basic principles of ethics of accounting professionals according to the regulations of the Federation of Accounting Professions regarding ethics for accounting professionals of Accounting Profession Organization 2018 with a statistical significance at the 0.05 level.